Locating Biomedicine in China: the Development of the Division of Pediatrics in Peking Union Medical College Hospital(1922—1942) - GU Xiaoyang; MA Mingsheng; SONG Hongmei (Xiehe Yixue Zazhi, 2022)
The division of pediatrics in Peking Union Medical College Hospital(PUMCH)is one of the birthplaces of modern pediatrics in China. Many excellent pediatricians have studied and worked there. It played an important role in the history of modern pediatrics in China. This study traced the history of pediatrics in PUMCH, using the annual reports and personnel files as main source materials. Other historical materials such as medical theses, memoirs, and second-hand materials were also studied. The purpose of this paper is to deepen the study of the history of Peking Union Medical College and PUMCH, enrich the research on the history of pediatrics in China, and better understand the development of medicine and the society of modern China.